Synthesis of 2,7,8-trioxaspiro[4,5]decan-1-ones by manganese(III)-based reaction - Ha, Nguyen Van; Han Hoan, Ta Thi; To Uyen, Nguyen Thi; Truc, Huynh Thanh; Nishino, Hiroshi (Vietnam Journal of Chemistry, 2017)
Some new spiro bicyclic compounds possessing one 1,2-dioxane ring and one γ-lactone ring were successfully synthesized by manganese(III)-based reaction of 1,1-diarylethenes and 2-acetylbutyrolactone under air. The procedure was simple and the product yield was high.   The NMR spectrometric features of the products were analyzed and the reaction mechanism is briefly discussed. Keywords. Manganese(III)-based reaction, spiro bicyclic compound, 1,2-dioxane ring, γ-lactone ring.